Tetanus in adults: results of the multicenter ID-IRI study - Tosun, S; Batirel, A; Oluk, A I; Aksoy, F; Puca, E; Bénézit, F; Ural, S; Nayman-Alpat, S; Yamazhan, T; Koksaldi-Motor, V; Tekin, R; Parlak, E; et al. (European journal of clinical microbiology & infectious diseases, 2017)
Tetanus is an acute, severe infection caused by a neurotoxin secreting bacterium. Various prognostic factors affecting mortality in tetanus patients have been described in the literature. In this study, we aimed to analyze the factors affecting mortality in hospitalized tetanus patients in a large case series. This retrospective multicenter study pooled data of tetanus patients from 25 medical centers. The hospitals participating in this study were the collaborating centers of the Infectious Diseases International Research Initiative (ID-IRI). Only adult patients over the age of 15 years with tetanus were included. The diagnosis of tetanus was made by the clinicians at the participant centers. Izmir Bozyaka Education and Research Hospital's Review Board approved the study. Prognostic factors were analyzed by using the multivariate regression analysis method. In this study, 117 adult patients with tetanus were included. Of these, 79 (67.5%) patients survived and 38 (32.5%) patients died. Most of the deaths were observed in patients >60 years of age (60.5%). Generalized type of tetanus, presence of pain at the wound area, presence of generalized spasms, leukocytosis, high alanine aminotransferase (ALT) and C-reactive protein (CRP) values on admission, and the use of equine immunoglobulins in the treatment were found to be statistically associated with mortality (p < 0.05 for all). Here, we describe the prognostic factors for mortality in tetanus. Immunization seems to be the most critical point, considering the advanced age of our patients. A combination of laboratory and clinical parameters indicates mortality. Moreover, human immunoglobulins should be preferred over equine sera to increase survival.
Keywords: senioři; analýza přežití; senioři nad 80 let; Retrospective Studies; Survival Analysis; Prognosis; mladiství; Risk Assessment; Middle Aged; mužské pohlaví; Adult; mladý dospělý; Aged, 80 and over; tetanus; Young Adult; ženské pohlaví; prognóza; hodnocení rizik; zvířata; retrospektivní studie; Humans; lidé středního věku; Hospitalization; hospitalizace; dospělí; Female; Aged; Adolescent; Tetanus; lidé; Male; Animals